Caracterización de la conducta antisocial y delictiva en condenado por hurto (2023)
The purpose of this research was to establish the psychocriminogenic characteristics of J.A.A.B., a man convicted for the crime of theft in the city of Barranquilla, Colombia and held in the "Establecimiento Penitenciario de Mediana Seguridad y Carcelario [EPMSC] - Cárcel del Bosque". In order to achieve this objective, a descriptive case study was designed to characterize the psychocriminogenic elements of the proposed case through the generation of a profile that integrates aspects related to personality, mental state, criminal history and formulations of the possible origins of criminal behavior from different positions. For the above, a mixed research methodology was implemented with qualitative elements for the analysis of interviews and quantitative elements that allowed us to analyze the results of each of the psychological instruments used in the evaluation of the person deprived of liberty.